Enhancing Internal Locus of Control in Young Children through Play Activities: A Case of Model-Preschool, Haramaya University, Ethiopia - Shumetu, Misahun Taye; Regassa, Tesema Regassa (Universitas Negeri Semarang, 2023)
This study aimed to investigate the practice of play activities in enhancing the internal locus of control among young children at Haramaya University's Model-Preschool. Employing a qualitative approach with an intrinsic case study design, data was obtained through semi-structured interviews with four preschool teachers, one preschool principal, and observation of play activities. The data was analyzed through the thematic data analysis technique, from which three major themes emerged: utilization of play activities, teachers' participation in facilitating play activities, and challenges encountered while facilitating play activities. The study's finding indicate that various play activities, such as open-ended play, problem-solving play, and creativity play, are employed to promote this crucial developmental skill. The preschool teachers reported employing a range of strategies to facilitate play activities that foster an internal locus of control, such as providing children with choices and constructive feedback. However, bottlenecks such as an inaccessible school environment, large class sizes, inadequate preschool teacher training, and insufficient resources were also identified as limiting factors in facilitating play activities that encourage an internal locus of control. Ultimately, the research concludes that participation in play activities can effectively aid in the development of young children's internal locus of control. Teachers who intentionally provide children with opportunities to make decisions, solve problems, and receive positive feedback can assist in cultivating a sense of self-efficacy and the conviction that they have control over their own outcomes.